Tenascin-C fibronectin D domain is involved in the fine-tuning of glial response to CNS injury in vitro - Bijelić, Dunja; Adžić, Marija; Perić, Mina; Reiss, Gebhard; Milošević, Milena; Andjus, Pavle R.; Jakovčevski, Igor (Frontiers in Cell and Developmental Biology, 2022)
Understanding processes that occur after injuries to the central nervous system is essential in order to gain insight into how the restoration of function can be improved. Extracellular glycoprotein tenascin-C (TnC) has numerous functions in wound healing process depending on the expression time, location, isoform and binding partners which makes it interesting to study in this context. We used an in vitro injury model, the mixed culture of cortical astrocytes and microglia, and observed that without TnC microglial cells tend to populate gap area in greater numbers and proliferate more, whereas astrocytes build up in the border region to promote faster gap closure. Alternatively spliced domain of TnC, fibronectin type III-like repeat D (FnD) strongly affected physiological properties and morphology of both astrocytes and microglia in this injury model. The rate of microglia proliferation in the region of injury decreased significantly with the addition of FnD. Additionally, density of microglia also decreased, in part due to reduced proliferation, and possibly due to reduced migration and increased contact inhibition between enlarged FnD-treated cells. Overall morphology of FnD treated microglia resembled the activated pro-inflammatory cells, and elevated expression of iNOS was in accordance with this phenotype. The effect of FnD on astrocytes was different, as it did not affect their proliferation, but stimulated migration of reactivated astrocytes into the scratched area 48h after the lesion. Elevated expression and secretion of TNF-α and IL-1β upon FnD treatment indicated the onset of inflammation. Furthermore, on western blots we observed increased intensity of precursor bands of β1 integrin and appearance of monomeric bands of P2Y12R after FnD treatment which substantiates and clarifies its role in cellular shape and motility changes. Our results show versatile functions of TnC and in particular FnD after injury, mostly contributing to ongoing inflammation in the injury region. Based on our findings, FnD might be instrumental in limiting immune cell infiltration, and promoting astrocyte infiltration of the injury region, thus influencing spaciotemporal organization of the wound and surrounding area.